Cross‐genera amplification of informative microsatellite markers from common bean and scarlet runner bean for assessment of genetic diversity in mungbean (Vigna radiata). Issue 4 (18th May 2016) - Pratap, Aditya; Gupta, Sanjeev; Tomar, Rakhi; Malviya, Nupur; Maurya, Ramanuj; Pandey, Vankat Raman; Mehandi, Suhel; Singh, Narendra Pratap
Abstract: Mungbean ( V. radiata ) is an important Asiatic legume supplying inexpensive protein to a vast majority of vegetarian masses. To increase markers repertoire in mungbean, a study was conducted to analyse 384 microsatellite markers derived from common bean, scarlet runner bean and adzuki bean for their transferability and polymorphism. The results showed that 87 (24.71%) primer pairs could amplify DNA loci of 20 mungbean genotypes including one accession of V. trilobata, while 52 showed reliable banding and polymorphism. These showed different degrees of variability at each locus producing 250 alleles with the number of alleles varying from 2 to 9. The major allele frequency varied from 0.17 to 0.95, while the polymorphic information content of SSRs ranged between 0.09 and 0.86 with an average of 0.60 ± 0.16. UPGMA revealed three major clusters accommodating 95% of the accessions while one accession of V. trilobata ('NSB‐007') did not group with any other genotype describing the discriminating power of informative microsatellites. This study identified a set of useful microsatellite markers to accelerate the genetic studies and breeding programme of mungbean.